KINSHIP ANALYSIS OF GRASS JELLY IN REGENCY OF GIANYAR, TABANAN AND BADUNG BASED ON MORPHOLOGICAL AND ANATOMICAL CHARACTERISTIC - Mursafitri, Eka Budi; Kriswiyanti, Eniek; Sutara, Pande Ketut (Jurnal Biologi Udayana, 2016)
Grass jelly is one of the plants that has considerable potential as medicine and drinks. This study was conductedto determine how kinship plant species Grass jelly from three districts. The Exploration of Grass jelly plantsconducted in Gianyar, Tabanan and Badung, Bali province. Making preparations in the Structures Laboratory ofPlant Development (SPT) Faculty Udayana University and the Center of Veterinary (BBVet). This research wascarried out from September 2015-January 2016. This research method using the technique of embedding andfresh slices, FAA fixative (formaldehyde: glacial acetic acid: alcohol 70% = 1: 1: 9), 1% safranin staining in 70%alcohol. For the analysis of kinship qualitative and quantitative data were suspended leaf anatomical charactersto create table Taxonomy Operation Unit (OTU). The results are used OTU table into mini-tab program version14.The result showed that four species of grass jelly plants are Cyclea barbata, Stephania japonica, Stephaniacapitata and Cocculus orbiculatus. Leaf form is like shields and ellipse. Kinship four types of plant grass jellyfrom three districts are very much based on morphological and anatomical characters (level 15.64% similarity).
Keywords: Grass jelly, analyze kinship, embedding, identification